PENGARUH LITERASI KEUANGAN, GAYA HIDUP, DAN PENDAPATAN TERHADAP KKEMAMPUAN PENGELOLAAN KEUANGAN PRIBADI MAHASISWA GENERASI Z - Agus Wahyudi Salasa Gama; Luh Buderini; Ni Putu Yeni Astiti (KRISNA: Kumpulan Riset Akuntansi, 2023)
The current era of globalization has brought improvements and economic growth throughout the world, including Indonesia which has an impact on people's financial behavior in meeting their needs. Individuals must be able to manage their finances carefully in order to make the right and efficient decisions in the use or allocation of funds they have. This study aims to find out how financial literacy, lifestyle, and income influence the personal financial management ability of Z generation students which will be carried out on Unmas Denpasar students. The samples of this study are 91 students of Universitas Mahasarsawati Denpasar, Faculty of Economics and Business, Management Study Program, class of 2019, which were taken using a saturated sampling technique. The data analysis technique used in this study is multiple linear regression analysis. The results of this study indicate that financial literacy, lifestyle, and income have a positive and significant effect on the personal financial management ability of Z generation students